## April 30, 2011

### Answer of 6÷2(1+2) is ...

Here is a simple maths for you..

whats the answer of 6÷2(1+2) = ?

Solution 1:

6 / 2 (1+2) = ?
Step 1: Solve what's inside the parenthesis first
(1+2) = 3
Step 2: Replace values
6/2(3) = ?

Step 3: Solve the division (we must solve it from left to right)
6/2 = 3

Step 4: Replace values, then multiply
3(3) = 9

------------------------------------------------------------------------------------- Solution 2:

Description: This is how we are taught at school, sadly we don't like solving it this way, so we got stuck in solving equations in the simplest way.

Step 1: Write the equation properly
6
- (1 + 2) = ?
2

Step 2: Solve what's in the parenthesis
(1 + 2) = 3

Step 3: Replace
6
- (3) = ?
2

Step 4: In clockwise motion, multiply 6 to the value on its right 6*3 = 18
Step 5: In clockwise motion, divide the answer from Step 4.
18 / 2 = 9

The answer for both solution is "9"

shooterboss said...

6/(2(1+2))
=6/(2(3))
=6/(6)
=1

Calvin said...

6÷2(1+2) =
6÷2(3) =
6÷2(1+2) =
3(3) =
9

Robert said...

6÷2(1+2) =
3(1+2)=
3(3)=
9

gknudsen said...

George said do the work in parenthesis first: (1+2)= 3

6/2*3

Then you can do the division either individually or multiply the 2 and the 3 to get 6 and then divide to get the answer 1

Anonymous said...

1

ivanatora said...

Oh, no... Not the "guess order of operations" again.

Secret Squïrrel said...

You don't have to "guess" the order of operations - they are clearly stated.

Parentheses (brackets) working from most deeply nested outwards, then indices (powers), then multiplication and division (equal priority), then addition and subtraction (equal priority). "Equal priority?" you say, "So how do I know which one to do first?". Obviously you're forgetting the other rule - work from left to right.

So 6÷2(1+2) = 6÷2×(3) = 3×3 = 9

2004 Chevrolet Astro Van AC Compressor said...

6/2(2+1)
6/6
1

Michelle Jones said...

The different opinion with the answers shows that people's understanding of math isn't always the same.

jude said...

9

Anonymous said...

6/2(2+1)
6/6
1

Anonymous said...

PEMDAS geee's

Parentheses 6/2(1+2) --> 6 / 2 * (3)

Exponents --> none

Multiplication/Division
6 / 2 * (3) --> 6/6 (the 3 in parentheses multiplies out first...)
No other way...but wrong

then Divide!

Those that divided the 6/2 -- don't build anything for me!

CIVIL ENGINEERING -- Georgia Tech

ThomasJPitts said...

1

Anonymous said...

1 pemdas

pankaj said...

ans is 1 or 9 because first we have to solve bracket the only then only we can do anything like dividing or multiply
so it can be 1 or 9

Anonymous said...

6/2(1+2)
6/2(3)
3(3)
9

Multiplication does NOT necessarily come before division. The rule for determining which to evaluate first is to do it from left to right. Also, grouping symbols (such as parentheses) only get precedence when operating within them, not on the group as a whole.

Anonymous said...

For all of you that say you have to multiply the 3 to the 2 before dividing just because it is in parenthesis are just plain dumb. You could put every single one of those numbers into parenthesis and still end up with the EXACT same problem. When it comes down to the multiplication and division, it is done from left to right even if there is a solo number in parenthesis.

soumyabrat said...

ans is 1 .no doubt at all.

Viraj Shah said...

6/2(1+2)=
6/2(3)=
3.~3=
9
9 is the correct answerget that straight.

Anonymous said...

MY CALCULATOR IS TRIUMPHANT. THE MIGHTY DEVICE SAYS THE ANSWER IS NINE.
It is nine, people.

And besides, why is everyone getting all worked up about a silly little math problem?

B.Lapko said...

Distributive Law of Multiplication
Answer must be 1, it's predicated on the aforementioned LAW.

Anonymous said...

I think it is 6.
6÷2(1+2)=6/2*3 = 6/2*3/1 = 12/2=6

chaitu said...

using BODMAS, 1 is the ans

Anonymous said...

I have two solutions that will both end up with the answer "9".

SOLUTION 1:
6 / 2 (1+2) = ?

Step 1: Solve what's inside the parenthesis first
(1+2) = 3

Step 2: Replace values
6/2(3) = ?

Step 3: Solve the division (we must solve it from left to right, MDAS is just a term used for kids to remember the rules in solving mathematical equations)
6/2 = 3

Step 4: Replace values, then multiply
3(3) = 9

SOLUTION 2:
Description: This is how we are taught at school, sadly we don't like solving it this way, so we got stuck in solving equations in the simplest way.

Step 1: Write the equation properly
6
- (1 + 2) = ?
2

Step 2: Solve what's in the parenthesis
(1 + 2) = 3

Step 3: Replace
6
- (3) = ?
2

Step 4: In clockwise motion, multiply 6 to the value on its right
6*3 = 18

Step 5: In clockwise motion, divide the answer from Step 4.
18 / 2 = 9

The answer for both solution is "9"

BEDMAS rule.... ANS. 9

Anonymous said...

9

John said...

9

Anonymous said...

Is it really that bad at Georgia Tech?

Shae said...

Definitely 9. People keep trying to convince me that the answer is 1 but I'm not swaying.

Anonymous said...

6 / 2 (1 + 2) = 6 / (2*1 + 2*2) = 6/6 =1

Anonymous said...

Last poster wanted to distribute the two but forgot you'd have to include the "6/" with it. So it would be:
6/2(1+2)= 3(1+2) = (3*1+3*2) = 3+6 = 9

The reason this is confusing is because of the division symbol isn't usually written in this form for real math, and something next to parenthesis is just shorthand for multiply. It's less confusing if you wrote it this way:

6/2*(1+2) or even better would be 6*1/2*(1+2)

Anonymous said...

Perhaps you see the ambiguity better if you start with 6/6 going backwards:
1 = 6/6 = 6/(2+4) = 6/2(1+2) = 6/2*(1+2) = 3 * (3) = 9

Anonymous said...

6÷2(1+2)=?
6÷2*1+2*2=?
6÷2+4=?
3+4=7

Danni said...

I am the only person who got this but could it be:
6÷2(1+2)
The multiply out brackets
6÷ (2x1)+(2x2)
6÷2+4
3+4
7
This is probably wrong but oh well.

Anonymous said...

6/2(1+2
Simple order of ops - PEMDAS or GEMDAS
1+2 = 3
6/2(3)
6/2 = 3
3(3)
9

Jimmy said...

In PEMDAS formula, which comes first wether multiplication/division, u do it first. So in this problem, 6/2(3), u should divide 6/2 first like addtion and substraction, whichever comes first u do first.

Onlyteng Num said...

1/2sqrt(3) = ?
1/2*SQRT(3) = ?

Tomas said...

2(3) has the result of 2x3. But it has higher priority than 2x3 or 6÷2

Tomas said...

also, 2(1+2) = (2(1+2))
but, 2(1+2) ≠ 2x(1+2) in this problem.

Xhoni Qazimi said...

Dude... There is not a 2x(3)... It is just 2(3)
So say it by words: Number six is devided by the duble of the sum 1+2.... It could be different if there was 6:2x(1+2)

mg hegde said...

Reply is 9. It is correct.

Anonymous said...

6/2(1+2)
=6/(2x1 + 2x2)
=6/2 + 4
=3 + 4
=7

Javkar DJ said...

You can't devide 6 by 2
Because 2 comes with bracket 1+2
=6/2 (1+2)
=6/(2+4)
=6/6
=1

Anonymous said...

6÷2(1+2)
= 6÷2x3 (parenthesis)
=3x3 (Divide and Multiply rank equally (and go left to right).)
=9

6÷2x3 means (6/2)x3 not 6/(2x3)

Anonymous said...

Okay so I'm confused. I got 7.
You have 6/2(1+2) right? Why not distrubute
6/(2*1+2^2) to get 6/2+4? Then 6/2 is 3. 3 plus 4 is 7. I'm really confused rn because I though anything in a(b+c) form equaled ab+ac. Can someone tell me why this isn't correct?

Anonymous said...

6/2(1+2)
6/2(3)

Evaluate 6/2 first since Division and multiplication are in the same precedence, follow left to right rule.

3(3)
9

Unknown said...

(6/2)(1+2) = 9, but 6/2(1+2) = 1 bcoz multiplication come
b4 division
6/2(1+2) =
6/2(3) = this is where multiplication is done first rather than division
6/6 = 1

When you bring in the factor of 2.
6/(1*2+2*2)
6/(2+4)
6/6
1

The debate is about when did you leave/convert () into *.

Some say 6/2*3, while others say 6/(2*3)

collin namindo said...

BODMAS
6/2(1+2)
=6/2(1)+2(2) B odmas
=6/2+4 bo D mas
=3+4 bodm A s

Anonymous said...

Pemdas screwed everyone e up lmao it's 9 I asked my.mstj professor

Unknown said...

Can someone explain why it doesn't equal 7?
6÷2 (1+2) to get rid of the parentheses shouldn't you multiplyou the 2 by 1 and 2?
6÷2×1+2×2
6÷2+4
3+4
7

Reynaldo Sarmiento said...

for as long as we do not see the mathematical expression 6/2(1+3) as a fraction we will not be able to reduce it, thus

6
______
2 (1+2)

6
_____
(2+4)

6
_____
6

1

we just did.

Anonymous said...

6/2(1+2)=x
2(1+2)=6x
2+4=6x
6=6x
x=1